A note on food consumption and growth of common dolphins (Delphinus delphis) - Kastelein, R.A.; Macdonald, G.J.; Wiepkema, P.R. (J. Cetacean Res. Manage., 2000)
Food consumption, body weight and body length were recorded in four female common dolphins (Delphinus delphis) at Marineland of New Zealand between 1974 and 1996. The study is based on historical data that were recorded for short-term husbandry purposes. The composition and caloric value of the diet sometimes varied from day to day. The food intake quantities should therefore be viewed as rough weight estimates of what wild conspecifics might eat (depending on their diet). Annual food intake of two dolphins increased to 3,300kg at around 12 years of age, after which it decreased, stabilising at around 2,200kg between the ages of 16 and 25 years. Annual food intake of the other two animals increased to 2,700kg at six/seven years of age, then declined and stabilised at around 2,100kg between the ages of seven/eight and 12 years. The weights of two of the animals were first recorded at the ages of seven and eight years. During the following 19 years, their body weight gradually increased by about 15kg. The other two animals grew from around 57kg at the age of two/three years to about 100kg at around 12 years of age. The two animals grew much in length when they were between two and eight years old. The other two animals appeared to have reached asymptotic length by 18 and 19 years of age when their length was measured for the first time. As body weight increased, daily food consumption as a percentage of body weight decreased. At a body weight of around 60kg, the dolphins consumed the equivalent of around 12% of their body weight per day. When body weight had reached around 100kg, daily consumption had fallen to around 6% of body weight.